P068 Computational fluid dynamic study in Obstructive Sleep Apnea patients. (9th November 2022) - Lee, Y; Lim, W; Jung, S; Lee, D
Abstract: Introduction: Obstructive sleep apnea (OSA) is a common disorder which may need surgery to widen the airway. However, the success rate of surgery is variable. Thus, it is necessary to predict the outcome of the surgery preoperatively. The purpose of this study is to evaluate the mechanical parameter of upper airway airflow in OSA patients using computational fluid dynamics (CFD) method. Method: We conducted a study on the patients with snoring, underwent the full night polysomnograpny (PSG) and paranasal sinus computed tomography(CT). The patients with past history of previous trauma or surgery were excluded. Three-demensional reconstructions of the upper airway were created in the medical imaging software Mimics 16.0 using paranasal CT. The reconstructions extended from nasopharynx to hypopharynx. Steady-state, turbulent, inspiratory airflow simulations were conducted in Fluent 17.0 with following boundary conditions The mechanical parameters (wall shear stress, pressure, plane velocity) were calculated in the three levels of nasopharynx, retropalatal, retrolingual area. Results: The maximum wall shear stress values were shown at the retropalatal plane in all patients. There is a tendency for the wall shear stress value of the retropalatal area to increase as the AHI increases. The maximum velocity values were shown at the retropalatal plane in all patients. The maximum pressure values were shown at the nasopharynx plane in all patients. Conclusion: the maximum wall shear stress values were shown at the retropalatal plane and the wall shear stress value of the retropalatal area increased as the AHI increased. Thus, the palatal surgery might help the OSA patients.